The Field of Musical Improvisation - Cobussen, Marcel (Leiden University Press, 2017)
The central aim of this book is to present a new approach to "the field of musical improvisation" (FMI), a theory which understands improvisation as a nonlinear dynamic and complex system. The study provocatively argues that during an improvisation more actants are "at work" than musicians alone: space, acoustics, instruments, audience, technicians, musical and socio-cultural backgrounds, technology, and the like all play a significant role. However, not all of these actants determine every improvisation to the same extent; some are more prominent and active than others in certain situations (periods, styles, cultures, as well as more singular circumstances). Therefore, the FMI theory will prove to be more than a theory dealing with improvisation "in general". Rather, FMI emphasizes singularity: each improvisation thus yields a different network of actants and interactions, a unique configuration or assembly.